DAILY ACTIVITIES OF LITTLE EGRET (Egretta garzetta) AT SERANGAN ISLAND, BALI - RIZKI SYAHPUTRA, M. RHEZA; GINANTRA, I KETUT; Raka Dalem, AA. Gde (Jurnal Biologi Udayana; Vol 22 No 1 (2018): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2018.v22.i01.p01, 2018)
A study on activity of the Little Egret (Egretta garzetta) was conducted in Serangan Island, southern part of Bali between May and June 2016. The aim of this study was to find out daily activities of these birds in three different habitats: lagoons, mangrove forests and muddy beaches. Preliminary observation was conducted through Ad Libitum sampling, while the sample on the main study was through a scan sampling method. The data was collected through recording activities of the egret on interval of 30 seconds within two hours. The data collection was undertaken in three periods: morning, afternoon and evening. The colony of observed egrets was chosen randomly across habitats and time periods. Data collected were descriptively or quantitatively analysed. Results of the study showed that from the three observation periods, the egret activities were dominated by the same activities, that was foraging, but with different magnitudes or percentages. In contrast, activities with the lowest percentage was agonistic. In the lagoon area, the percentage of the activity of foraging was as follows: in the morning it was 50.15%, in the afternoon 46,62%, and in the evening 49,63%. In mangrove areas the percentage of foraging activities was as follows: in the morning it was 52.46%, in the afternoon 41.60%, and in the evening 50.83%. The percentage of foraging activities in muddy beaches was as follows: in the morning it was 50.18%, in the afternoon 42.70%, and in the evening 49,65%. Keywords : little egret, Serangan Island, daily activities, habitat, Bali